Research on basic mechanical properties of different modulus alkaline excited ECC - Che, Jialing; Yang, Renze; Wang, Jun; Liu, Haifeng; Hu, Yun xiang; Doh, Shu Ing (Elsevier Ltd, 2022)
The effect of the alkali activator modulus on the mechanical properties and microstructure of two types of fiber-reinforced engineering cementitious composites (alkali-excited ECC) with desert sand as fine aggregate was studied. The alkali activator was prepared by a certain proportion of NaOH and sodium silicate mixture, and the mechanical performance indexes were used for analysis, including compressive/tensile/flexural strength, Poisson's ratio and elastic modulus, flexural toughness ratio and energy performance index (PSH). The results showed that the appropriate alkali activator modulus was conducive to improving ECC mechanical performance. The indexes of the high water-to-binder ratio alkali-excited ECC and the low water-to-binder ratio alkali-excited ECC were the best when the alkali activator modulus of 1.5 and 2, respectively. Under the same modulus of alkali-activator, the compressive and flexural strengths of two types of alkali-excited ECC specimens increased with age, and PSH of low water-to-binder ratio alkali-excited ECC specimens increased with age. SEM results showed that after the action of alkali activator, the substrate surface of alkali-excited ECC was attached with colloidal substances. Combined with EDS and XRD hydration analysis, the hydration products were mainly C–S–H, C-A-H and Ettringite.